Socio-demographic factors associated with chhaupadi practice among adolescence girls of Mangalsen Municipality, Accham Nepal - Thapa, Roshan Kumar; Chhetri, Mamta; Paudel, Amrita; Koirala, Subash; Poudel, Eak Narayan; Adhikari, Kishor (Journal of Chitwan Medical College, 2021)
Background: Chhaupadi practice, which is characterized by banishment of women during menstruation from their usual residence due to supposed impurity. The Chhaupadi custom is also known as ‘chhue’or ‘bahirhunu’ in Dadeldhura,Baitadi and Darchula,as Chhaupadi in Acham, and as ‘chaukulla’or ‘chhaukudi’in Bajhang district.The aim of the study was to find out Socio demographic factors associated with Chhaupadi practices among adolescence girls of Mangalsen Municipality, Acham Nepal. Methods: The community based descriptive cross-sectional study using face to face interview was carried out in Mangalsen Municipality, Acham Nepal. 221 adolescence girls (10-19) years were selected by simple random sampling. The total duration of data collection was one month from 2074/01/07 to 2074/02/08. Data were collected using self-designed semi structured questionnaire. Collected data were manually checked then entered into IBM SPSS version 20.0 for Window. We used Pearsons chi-square test is used to investigate the effect of Socio-demographic variable on Chhaupadi practices during last menstruation period of adolescent. Results: Among 221 adolescent girls, there were 84.2 %(186) of the respondents were kept in Chhaupadi or slept at Chhau goth during entire last time menstrual period, Socio-demographic characteristics such as age (χ2=8.997, 0.001), mother educational level(χ2= 6.80, p=0.033), occupational status of respondent’s mother (χ2=4.20, p=0.04) ,type of family(χ2=5.20, p=0.022) were found to be significantly associated with Chhaupadi practice . Conclusions: Majority of the adolescent girls are still practicing Chhaupadi during menstrual period. Chhaupadi practice continues to exits in community because of illetracy,traditional belief system.To abolish Chhaupadi practice awareness and education at community level is required.